Ratio Decidendi Dalam Putusan Majelis Hakim Nomor 63/Pid.B/2021/PN/Skm Pengadilan Negeri Suka Makmue - Kakey Khadafi Al Hafidz; Muhammad Dimas Setiadi (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
An independent judiciary is one of the fundamental principles of a state governed by the rule of law, where judges are required to adjudicate cases independently, objectively, and fairly. In criminal justice practice, judicial legal reasoning known as ratio decidendi plays a crucial role as it constitutes the core legal rationale that determines the operative part of a judgment. This article aims to analyze the ratio decidendi of the Panel of Judges in the Decision of the Suka Makmue District Court Number 63/Pid.B/2021/PN.Skm, which applies a restorative justice approach through the recognition of customary law settlement in the form of the peusijeuk traditional ceremony. This study employs a normative legal research method with statutory, conceptual, and case study approaches to court decisions. The findings indicate that the Panel of Judges based its legal considerations on living law values within the community, the principles of restorative justice, and the doctrine of ne bis in idem to prevent the imposition of double penalty on the defendant. The application of customary law in the court’s consideration is deemed proportionate and equivalent to criminal sanctions, rendering formal criminal punishment no longer reflective of a sense of justice. Therefore, this decision demonstrates the active role of judges in exploring and applying living law within society as part of the ratio decidendi to realize substantive justice in Indonesia’s criminal justice system. Keywords: Ratio Decidendi; Restorative Justice; Judicial Independence; Customary Law. Abstrak Kekuasaan kehakiman yang merdeka merupakan salah satu prinsip fundamental dalam negara hukum, di mana hakim dituntut untuk memutus perkara secara independen, objektif, dan berkeadilan. Dalam praktik peradilan pidana, pertimbangan hukum hakim yang dikenal sebagai ratio decidendi memegang peranan penting karena menjadi inti penalaran hukum yang menentukan amar putusan. Artikel ini bertujuan untuk menganalisis ratio decidendi Majelis Hakim dalam Putusan Pengadilan Negeri Suka Makmue Nomor 63/Pid.B/2021/PN.Skm yang menerapkan pendekatan restorative justice melalui pengakuan terhadap penyelesaian hukum adat berupa prosesi adat peusijeuk. Penelitian ini menggunakan metode penelitian hukum normatif dengan pendekatan perundang-undangan, konseptual, dan studi kasus terhadap putusan pengadilan. Hasil penelitian menunjukkan bahwa Majelis Hakim mendasarkan pertimbangannya pada nilai-nilai hukum yang hidup dalam masyarakat, prinsip keadilan restoratif, serta asas ne bis in idem guna menghindari terjadinya double penalty terhadap terdakwa. Penerapan hukum adat dalam pertimbangan tersebut dipandang sepadan dan sebanding dengan sanksi pidana, sehingga penjatuhan pidana formal dinilai tidak lagi mencerminkan rasa keadilan. Dengan demikian, putusan ini menunjukkan peran aktif hakim dalam menggali dan menerapkan hukum yang hidup di masyarakat sebagai bagian dari ratio decidendi guna mewujudkan keadilan substantif dalam sistem peradilan pidana di Indonesia. Kata kunci: Ratio Decidendi; Keadilan Restoratif; Kebebasan Hakim; Hukum Adat.